Crystal growth, optical, photoluminescence and magnetic properties of sol-gel GdFeO3 thin film - Baqiah, Hussein; Zhang, Na; Awang Kechik, Mohd Mustafa; Mohammed Al-Hada, Naif; Kiong Tiong, Sieh; Al-Zahrani, Asla A.; Liu, Jian; Li, Qiang; Xu, Shicai (Elsevier, 2024)
GdFeO3 (GFO) orthoferrite is a perovskite structured material with rich physical properties. In this work, crystal growth, electronic, optical, photoluminescence (PL) and magnetic properties of sol-gel synthesized GFO thin films onto quartz substrate were investigated. The films were annealed at various temperature 650–900 °C. XRD results showed transformation from an amorphous to nanocrystalline GFO and GdO secondary phase with rise of annealing temperature from 650 to 700 °C. Single phase GFO was observed in films annealed above 700 °C. Crystallite size of the films gradually increased from 10.5 to 89.9 nm for films annealed from 700 to 900 °C, respectively. The surface morphology changed from porous microstructure consisted of tiny particulates in film annealed at 700 °C into enlarged particles and clear polycrystalline structure in films annealed above 700 °C. From XPS spectra analysis, both Fe and Gd ions existed in a 3+ valence state. The films demonstrated optical band gap ranged between 2.8 and 3 eV. The PL spectra obtained using a 300 nm excitation wavelength consisted of four emission peaks. The near band edge emission of the films varied between 449.9 and 455.1 nm. The films showed weak ferromagnetic behavior with magnetization ranging from 24 to 49 emu/cm3.